2023
DOI: 10.1186/s13039-023-00636-2
|View full text |Cite
|
Sign up to set email alerts
|

Identification of complex and cryptic chromosomal rearrangements by optical genome mapping

Abstract: Background Optical genome mapping (OGM) has developed into a highly promising method for detecting structural variants (SVs) in human genomes. Complex chromosomal rearrangements (CCRs) and cryptic translocations are rare events that are considered difficult to detect by routine cytogenetic methods. In this study, OGM was applied to delineate the precise chromosomal rearrangements in three cases with uncertain or unconfirmed CCRs detected by conventional karyotyping and one case with a cryptic t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…3,4 Here, we found that the high resolution of OGM makes it a promising method for detecting cryptic BCRs; our findings were in agreement with those of two other recent studies. 9,10 Detailed information about breakpoints is another superior characteristic of OGM when compared to karyotyping and FISH. 3,4 Although breakpoints identified by OGM were not directly validated using other methods, consistency with offspring rearrangements nevertheless underscored the reliability of OGM in identifying SV breakpoints.…”
Section: Case Presentationmentioning
confidence: 99%
“…3,4 Here, we found that the high resolution of OGM makes it a promising method for detecting cryptic BCRs; our findings were in agreement with those of two other recent studies. 9,10 Detailed information about breakpoints is another superior characteristic of OGM when compared to karyotyping and FISH. 3,4 Although breakpoints identified by OGM were not directly validated using other methods, consistency with offspring rearrangements nevertheless underscored the reliability of OGM in identifying SV breakpoints.…”
Section: Case Presentationmentioning
confidence: 99%